A Survey on Prediction of Suitable Crop Selection for Agriculture Development Using Data Mining Classification Techniques - Prathyusha K, Angel; Y, Mahitha; Kumar Reddy N, Prasanna; Rajeswari P, Raja (International Journal of Engineering and Technology, 2018)
Agriculture is analytically the vast economic sector and is an important aspect in the economic growth of India. It is the only cause of living for about two-thirds of the population in India. It is very essential for the farmers to choose a crop that best suits the land being used for cultivation. The criteria to be considered in order to decide the crops that best suitable for the land are soil, water and season. The best suitable crop for the land can be predicted based on the agriculture data collected from the agriculture experts or from the farmers. Our paper provides a survey of the various classification techniques and classifiers used for the prediction of suitable crop selection for agriculture development. Farmers should get benefited by cultivating the best fitting crops rather than cultivating the unsuitable crops.Â